THE INFLUENCE OF MUSIC PLAYING ON THE AESTHETIC PERCEPTION OF MUSIC BY YOUNGER SCHOOL STUDENTS - Вишневецька, М.В. (Modern engineering and innovative technologies, 2023)
The article highlights the pedagogical conditions for the formation of interest in music among elementary school students. The effectiveness of the influence of music games on the educational process and the formation of aesthetic perception of music is t